The Aftermath of Coup dâ Etat Against Mohammad Mosaddeq of Iran in 1953: Reflections from British Documents - Ebrahimi, Mansoureh; Yusoff, Kamaruzaman (TAWARIKH, 2011)
ABSTRACT: The present study investigates the Britainâs efforts after the 1953 coup in Iran. The mentioned coup is a vital milestone in the study of contemporary history of Iran. The coup that terminated to collapse Prime Minister Mohammad Mosaddeq from the power. Mosaddeq was arrested and imprisoned after the coup. The present article investigates two main targets. In the first place, it intends to study the British attempts in deciding to exterminate Mosadeqâs government. Secondly, it tries to elucidate the British strategies to deal with various events happened, particularly after the coup. The exact analysis has been used to examine how British documents have shed a new light to the history of the 1953 coup. The resultant study manifests that through the coup plan and via controlling the internal circumstances of Iran after the coup, British â supported also by the USA â were the most considerable factor in changing the domestic and foreign policies of Iran. KEY WORDS: The coup, Mosadeqâs government, British and USA strategies, and changing the domestic and foreign policies of Iran.===About the Authors: Mansoureh Ebrahimi and Kamaruzaman Yusoff are Lecturers at the School of History, Politics and Strategic Studies, Faculty of Social Sciences and Humanities UKM (National University of Malaysia), Bangi, Selangor Darul Ehsan, Malaysia. They can be reached at: kamaruz@pkrisc.cc.ukm.myHow to cite this article? Ebrahimi, Mansoureh & Kamaruzaman Yusoff. (2011). âThe Aftermath of Coup dâ Etat Against Mohammad Mosaddeq of Iran in 1953: Reflections from British Documentsâ in TAWARIKH: International Journal for Historical Studies, Vol.2(2) April, pp.203-220. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 13, 2011); Revised (March 17, 2011); and Published (April 28, 2011).